Dc chopper controller using personal computer/ Mohd Rashid Mohd Zain - Mohd Zain, Mohd Rashid (1998)
In this project, a simple PC controlled chopper circuit was developed to generate variable dc output voltages that can used for many industrial drive and process applications.Variable output voltages are generate by controlling the switching time of the chopper switching device controlled by the software written in Turbo C programming language. The hardware developed include a parallel interface system, digital analog converter and chopper converter system. The developed software is designed to provide reliable and flexibility in its operation so that any modification and alteration to the system operation can be done easily and coveniently